Pengembangan Multimedia Interaktif IPA SD Kelas IV Materi Makan dan Dimakan Antar Makhluk Hidup - Inawan, Dawam Sururi; Sulthoni, Sulthoni; Ulfa, Saida (Universitas Negeri Malang, 2022)
This development aims to produce interactive multimedia as a learning medium consisting of text, graphic arts, sound, animation, and video with the sub-discussion of the relationship between eating and eating between living things for the fourth grade natural education subject. This interactive multimedia can be used as an alternative in learning so that students are interested and motivated in learning. Interactive multimedia is presented in the form of an Exe for use via a personal computer. Details of the sub-discussion of the material and its appearance design are arranged in a User Friendly system to make it easier to use. This interactive multimedia research and development method uses the Sugiyono model. Response from media experts and material experts on interactive multimedia received a positive response. The trial of the use of interactive multimedia was also carried out on fourth grade elementary school students. Interactive multimedia learning is beneficial for teachers and students during learning activities, because the role of learning media is to help teachers and students in explaining and studying material in a straightforward and interesting way, interactive multimedia is worth using in learning.AbstrakPengembangan ini bertujuan untuk menghasilkan multimedia interaktif sebagai media pembelajaran terdiri atas teks, seni grafik, bunyi, animasi, dan video dengan sub bahasan hubungan makan dan dimakan antar makhluk hidup untuk mata pelajaran ilmu pendidikan alam SD kelas IV. Multimedia interaktif ini dapat digunakan sebagai alternatif dalam pembelajaran sehingga anak didik tertarik dan termotivasi dalam belajar. Multimedia interaktif disajikan dalam bentuk exe penggunaannya melalui personal computer. Rincian sub bahasan materi dan desain tampilannya disusun dengan sistem User Friendly agar memudahkan dalam penggunaannya. Metode penelitian dan pengembangan multimedia interaktif ini menggunakan model Sugiyono. Tanggapan dari ahli media dan ahli materi terhadap multimedia interaktif memperoleh respon yang positif. Uji coba pemanfaatan multimedia interaktif pun dilakukan kepada anak didik SD kelas IV. Pembelajaran multimedia interaktif bermanfaat bagi guru dan anak didik di saat kegiatan pembelajaran, karena peran media pembelajaran adalah membantu guru dan anak didik dalam menjelaskan dan mempelajari materi secara gambling dan menarik secara keseluruhan, multimedia interaktif layak dimanfaatkan di dalam pembelajaran.